Mapping the evolution of myocardial infarction research in communication studies: A comprehensive bibliometric analysis - BOZKURT, Emrah; URHAN, Bahar; ERTÜRK, Hülya Anakız; SERTKAYA, Sema (Edelweiss Applied Science and Technology, 2025)
This study aimed to systematically delineate and map the evolution of myocardial infarction research within the communication domain through a comprehensive bibliometric analysis. A total of 210 English-language articles, retrieved from the Scopus database spanning from 1967 to 2022, were analyzed using the Bibliometrix R software library and the VOSviewer visualization tool. The analysis revealed a marked surge in scholarly discourse on myocardial infarction within the communication field beginning in 2015. Geographically, the majority of contributions originated from developed regions, particularly North America and Europe, with the United States emerging as the most prolific contributor—accounting for 325 publications and 13,222 citations. The dataset comprised work from 819 distinct authors, with Kristiansen Is. identified as the most influential author and Davis Br. receiving the highest co-citation recognition. Among journals, Academic Medicine led in publication volume, whereas the American Journal of Emergency Medicine demonstrated the greatest influence. This study provides a panoramic overview of the myocardial infarction research landscape within the communication domain, highlighting key trends, influential contributors, and impactful publications. The findings underscore the critical intersection of interpersonal communication, risk management, and communication technologies in the context of myocardial infarction, offering valuable insights and a strategic roadmap for future research in this interdisciplinary field. This bibliometric analysis did not involve direct patient or public contributions.